Mechanism Of Regrinding In Rotary Cutting Machines - A. W. Khair; Danqing Xu (Society for Mining, Metallurgy & Exploration, 1991)
This paper presents an analysis of mechanism of secondary fragmentation and respirable dust generation due to regrinding. In continuous miners, the recovered coal and uncleaned coal from the previous cutting cycle have to be transported through the circumference of the cutting drum, subjecting the coal to regrinding. Such regrinding comminutes the coal material utilizing kinetic energy, thus creating a great amount of respirable dust. The mechanism of a single particle subjected to regrinding is analyzed. A mathematical model is developed to describe regrinding in field conditions. The important factors influencing the comminution process are discussed in detail. Utilizing three types of coal seams, laboratory experiments are being carried out with an Automated Rotary Coal Cutting Simulator (ARCCS) to quantitatively evaluate the effects of some particular parameters, such as cutting velocity, depth of sump and properties of coal material, on breakage and on the amount of respirable dust generated. An orthogonal fractional factorial experimental arrangement is used to optimize experimental design. Preliminary experimental results are presented.